ENTREPRENEURIAL UNIVERSITY: DEVELOPING AND INTEGRATING THE THIRD MISSION IN HIGHER EDUCATION INSTITUTIONS - Mihaela, DIACONU; Amalia, DUTU (Strategii Manageriale)
The modern unversity which activates in a highly competitive market and is mostly assisted and not financially supported by the state must find tools with which to be competitive and prestigious. It is necessary to identify the managerial and scientific opportunities with which to build the best resources in order to fulfill its mission. This study presents the role of the university in the economic and social environment supported by the mission undertaken by three components: teaching, scientific research and the social function and to what extent the third mission of the modern university is seen as a necessity in the context of current economic and social context by the universities of Romania. The method used was the content analysis of the mission of universities in Romania presented in the University Charter and its correlation with the analysis models on entrepreneurship and academic entrepreneurial management offered by the specialized literature. The conclusion is that more than 60% of universities in Romania formulated their mission by considering the three components and that understanding and building entrepreneurial culture is a condition of the successful fulfillment of the mission of the modern university.